Peran Hutan Mangrove sebagai Biofilter dalam Pengendalian Polutan Pb dan Cu di Hutan Mangrove Sungai Donan, Cilacap, Jawa Tengah - Giska Parwa Manikasari; Ni Putu Diana Mahayani (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Cilacap Oil Refinery that produces heavy metal waste containing Pb and Cu is located across to themangrove forests along Donan river banks. This study aimed to recognize the role of mangrove forestas biofilters in controlling water pollutants of Pb and Cu that is predicted containing the mangroverehabilitation areas along Donan River banks, Cilacap. The research site was grouped into fourareas, which are control zone (three km before the point source), Inner Zone (at the point source),middle zone (one km point source), and outer zone (estuarine). Four plots were established tomeasure chemical water quality and mangrove tree density. Data colected were then analyzed usingregression model to identify the relationship between mangrove tree density and Pb and Cuconcentration in the water, substrate, roots, and leaves of Rhizophora apiculata. Analysis of variancewere applied among four zones to find out the role of mangrove as biofilters for those heavy metals.The results showed that even though Pb and Cu concentration in the water was not significantlydifferent, however, the concentrations of those heavy metals from the point source to the estuarinezones decreased, especially the concentration of Pb in the substrat highly reduced. Finally, the role ofmangrove forest as biofilter was also recognized from the concentration of Pb and Cu detected in theroots and leaves of Rhizophora apiculata.